Primary Dural Lymphoma: Clinical Cases and Literature Review - M. Dobran; R. Paracino; F. Mancini; D. Nasi (Case Reports in Medicine)
Primary dural lymphoma (PDL) is an extranodal non-Hodgkin lymphoma that accounts for less than 1% of all central nervous system lymphomas. Primary dural lymphoma grows from the dura mater, and it is often diagnosed as meningioma or acute subdural hematoma due to its radiological characteristics. Surgery is the gold standard of therapy; in many patients, PDL is relatively benign with good outcome. Authors report their experience in three patients affected by extranodal non-Hodgkin lymphoma (PDL) mimicking a meningioma.